Folk Handicrafts of the Ceramics City – Khurja: Reviving Folk Handicrafts in Khurja: Exploring Tradition and Market Trends (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is a country where history of crafts and traditions are very rich, legacy, heritage and cultural. Due to modernization and mechanization, a lot of crafts were slowly beginning to get lost in history, but the love of craft, design and tradition helped the revival of Indian Craft Industry. Ceramic products in ‘Khurja’ in the Bulandshahr district region of Uttar Pradesh are known all over the world where few products are made into some designer pieces or beautiful art wares or vases and others are made into variety of useful crockery’s.A detail study in this context shows an overview about the origin of the history of traditional Khurja’s folk handicrafts and its market culture throughout the world. A great contributory factor towards the setting up of the concentration of small scale ceramic industries in Khurja shows the positive attitude of the government of Uttar Pradesh. This paper explores the study of the evolution on folk handicraft of doab area with special emphasis on ‘Khurja’ which aims to trace the existence of the tradition of art practices of pottery making in ceramics and critically analyze the present market trends of pottery.